Effectiveness of artesunate combined with fractional CO2 laser in a hypertrophic scar model with underlying mechanism. Issue 3 (May 2022) - Zhang, Jinxia; Zhou, Shuanglin; Xia, Zhikuan; Peng, Zhuoying; Luo, Wanting; Cheng, Xiaoxian; Yang, Rongya
Highlights: To explore the pre-clinical significance and the underlying mechanism of artesunate (ART) and fractional CO2 laser (FCO2L), we first observe the expression of BMP-7 and Fas after this combined treatment. Histological and immunohistochemistry study, Western blot analysis, cell viability study, ELISA and RT-QPCR were performed at Week 10 to explore the changes of HS samples and the expression of BMP-7 and Fas. Our findings may pave the way for a potential alternative strategy to treat HS in clinical practice. Abstract: Background and objectives: Both artesunate and fractional CO2 laser have been proved effective in the treatment of hypertrophic scars, yet little data are available for the efficacy of artesunate combined with fractional CO2 laser. In order to assess the pre-clinical significance and the underlying mechanism of this combined treatment profile, we attempted to observe the effectiveness of this therapy in rabbit models through determining the expression of BMP-7 and Fas. Materials and methods: Twenty-Four New Zealand white rabbits with established hypertrophic scar samples were randomly divided into control group and three treatment groups. Artesunate (20 μl/cm 2 ) was injected into the rat's scar of artesunate and combination groups, while fractional CO2 laser (Combo mode, deep energy:10 mJ, super energy: 50 mJ) was applied to rats in fractional CO2 laser and combination groups at week 4 after model establishment. All rabbits underwent a total of 3 sessions of treatment once every 2 weeks. Histological and immunohistochemistry study, Western blot assay, cell viability, ELISA and RT-QPCR were performed at week 10 to observe the aspects of hypertrophic scar sample changes and expression of BMP-7 and Fas in the scar tissues. Results: Compared with control group, hypertrophic scars and the collagen fibers were significantly inhibited after treatment, and higher inhibition was seen in the samples in combination group compared to that in artesunate and fractional CO2 laser groups ( P < 0.01). Meanwhile, BMP-7 and Fas expressions were both notably increased in all treatment groups, and upregulation of the two proteins was dominant in combination group ( P < 0.01). Conclusions: Artesunate combined with fractional CO2 laser is effective in hypertrophic scarring in this rabbit model. Our findings can serve as a potential alternative strategy to treatment of hypertrophic scar in clinical practice.